(3cJGH GdSjQs - (3GdTeGNj , CMeO Hf SYjO Hf YHO GdhGMO GdjaQfj, HOQ GdOjf,J (B928 (3g` s ((3jMi Hf eMeO Hf jMji GdTeGNi GdfahSi s)
(3ChdgG (B:s
(3Ydi GdCfHGQ , hYdjg MSGf Hf MSGf abJdg s
(3BNQgG (B:s
(3hefge CHh YKeGf SYjO GdSOhjcTi , hGdYdeGA cKjQI (B[(3cPG(B] (3hPcQfG efge eG ajg GdcaGjI , hdjcf gPG BNQ GdJYQja Hge , hGdMeO ddg QH GdYdejf s
(3HOCg HSjQI GdfHj Udi Gddg Ydjg h Sde h GdNdaGA GdQGTOjf h HGbj GdUMGHI Ke GdJGHYjf hef HYOges
(3hef hLO ai YUQ gDdGA ef YdeGA GdCHGVjI hCTQGage hef fTQ ePgHge ef HOA CeQge Edi YgOg ai WQGHdS GdZQHs
(3hedMb HGdfSNI eLehY ai eTGgO LHd fahSI hPcQ eSGLOgGs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs